Reflection of National Worldviews in the Zoonymic Phraseology and Paremiology of Tuvans, Kazakhs, Russians, and Englishmen - Shingareva, Marina Yu.; Orynbetova, Elmira A.; Mezentseva, Yelena S.; Dmitryuk, Natalya V.; Temirbekova, Galiya A. (The New Research of Tuva, 2024)
The article compares the worldviews of the Tuvans, Kazakhs, Russians, and English, as reflected in the respective zoosemantic phraseology and paremiology. The study is based on phraseological units (PUs) and paremiological structures (PSs) containing zoosemantic components, collected through a systematic sampling from the relevant phraseological dictionaries and collections of proverbs and sayings of the compared languages. A statistical analysis was conducted on the most frequent zoosemantic nominations that appeared with similar frequency in the phraseological/paremiological corpora of the four languages. As a result, five animal nominations were selected for linguistic and cultural analysis within PUs and PSs: horse (kon’/a’t/a’t/horse); dog (sobaka/y’t/ym/dog); sheep (ovtsa/baran/khoy/koy/sheep); wolf (volk/boru/bory/kaskyr/wolf); and bird (ptitsa/kush/kys/bird). The novelty of the study lies in the ethnocultural comparison of zoosemantic PUs to uncover both specific and universal cultural information about the models of zoosemantic cultural-linguistic codes in the archetypes of the consciousness of the Tuvans, Kazakhs, Russians, and English. The study reveals that the comparison of zoocomponents in phraseological units and proverbs shows both shared (cross-cultural) and ethnospecific models of perceiving the animal world, which determine the patterns of figurative interpretation of surrounding realities and the specific ways of conceptualizing human perceptions of animals in different cultures.